2004
DOI: 10.1073/pnas.0401496101
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor screen in Mpl -/- mice: c-Myb mutation causes supraphysiological production of platelets in the absence of thrombopoietin signaling

Abstract: Genetic screens in lower organisms, particularly those that identify modifiers of preexisting genetic defects, have been used successfully to order components of complex signaling pathways. To date, similar suppressor screens have not been used in vertebrates. To define the molecular pathways regulating platelet production, we have executed a large-scale modifier screen with genetically thrombocytopenic Mpl ؊/؊ mice by using N-ethyl-N-nitrosourea mutagenesis. Here we show that mutations in the c-Myb gene cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
160
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(168 citation statements)
references
References 31 publications
6
160
2
Order By: Relevance
“…6A). The c-Myb 3M, PLT3, and PLT4 mutants possessed comparable activities with that of the WT in contrast to lower activity from the PLT4 mutant reported by Carpinelli et al (4). Surprisingly, the double-domain mutants (3M.CT3 and 3M.L3,4P) exhibited minimal transactivation ability, which was substantially less than that of the WT and CT3 Myb forms.…”
Section: Tad Mutants and Nrd/dbd Double Mutants Lose Transactivation contrasting
confidence: 40%
See 1 more Smart Citation
“…6A). The c-Myb 3M, PLT3, and PLT4 mutants possessed comparable activities with that of the WT in contrast to lower activity from the PLT4 mutant reported by Carpinelli et al (4). Surprisingly, the double-domain mutants (3M.CT3 and 3M.L3,4P) exhibited minimal transactivation ability, which was substantially less than that of the WT and CT3 Myb forms.…”
Section: Tad Mutants and Nrd/dbd Double Mutants Lose Transactivation contrasting
confidence: 40%
“…c-myb-null mice display abnormal fetal liver hematopoiesis and die by day 15 of gestation due to severe anemia (3). Moreover, ENU mutagenesis studies in mice revealed point mutations in myb that resulted in hypomorphic alleles and consequent hematopoietic irregularities (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Ski deficiency resulted in a high penetrance (83%) of exencephaly in a 129p2 background but a low penetrance (5-6%) in the C57BL6 strain (Colmenares et al, 2002). Genetic variation of NTDs in mouse likely reflects the additive effects of several mutant genes, and additional mutagenesis may be required to define factors that affect the penetrance of NTDs in the presence of defective alleles of Gcn5 (for example, see Carpinelli et al, 2004). Genetic variations also likely underlie different susceptibilities to NTDs in humans (Zohn et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Modifier screens have proven extremely powerful in yeast, worms, and flies to dissect complex biological questions. A dominant modifier screen in the mouse found two alleles that suppressed the lack of platelets found in Mpl homozygous deletion mice (Carpinelli et al, 2004). Modifier screens take time and careful planning, as mouse production must be ramped up so that there are enough animals available for the screening crosses.…”
Section: Perspectivementioning
confidence: 99%